(untitled) (Research, Society and Development, 2022)
As a result of the use of mechanized sugarcane harvesting, studies are needed that advocate the best operational and economic performance of the harvester. Therefore, the objective of this work was to evaluate the visible losses in the mechanized harvesting of sugarcane as a function of three rotations of the primary extractor of a self-propelled harvester (R1- 900 rpm, R2- 1,000 rpm and R3- 1,100 rpm) at speed operating time (4 km h-1). Data were analyzed using statistical process control (SPC), where control charts of individual values ​​and moving range were used to verify losses. Sixty sample plots of 13 m2 were used, spaced 50 m apart. Losses were separated, weighed, quantified, transformed into kg ha-1 and classified according to the methodology proposed by Reis (2009). Data were submitted to descriptive statistical analysis to verify normality and, subsequently, control charts of individual values ​​(CEP) were made to quantify the volume of losses and process instability. Therefore, under the working conditions, special causes acted in the harvesting process, making it unstable in terms of losses. The highest total losses were observed at the intermediate speed of 1000 rpm, followed by the highest speed at 1100 rpm.